Ground based observations of Pc3-Pc5 geomagnetic pulsation power at Antarctic McMurdo station - Ballatore, P.; Engebretson, M. J.; Maclennan, C. G.; Candidi, M. (Annals of Geophysics, 1998)
The two horizontal geomagnetic components and, measured by a fluxgate magnetometer at Antarctic McMurdo station (corrected geomagnetic coordinates 80.0° S, 327.5° E), are analyzed for the period May-June 1994; the spectral powers are calculated and integrated over three frequency intervals corresponding to the nominal ranges. The time dependence of those integrated powers and their correlations with northern auroral indices and solar wind speed are considered. The observations are compared with previous results reported from Terra Nova Bay station (located near McMurdo at the same corrected geomagnetic latitude) during Antarctic summer intervals. The differences found between the two stations are discussed in terms of the seasonal dependence of geomagnetic field line configurations in the near cusp region.